A resource-centric perspective on strategic and sustainable Corporate Social Responsibility (CSR) initiatives. (26th April 2010) - Bhattacharyya, Som Sekhar
Corporate Social Responsibility (CSR) has become an established mantra for business firms' to address social and environmental issues challenging the present-day world. CSR activities require firm resources. CSR initiatives in turn also generate resources of various qualities and varying quantity. It is indeed interesting to study the quality and quantity of resources dedicated for CSR activities and the resources generated from the CSR activities. The purpose of this paper is to develop a typology for resource based classification of CSR and provide a guiding framework to managers for planning CSR activities to make them strategic in nature.